Parental care compromises feeding in the pumpkinseed (Lepomis gibbosus) - Zięba, G; Dukowska, M; Przybylski, M; Fox, M G; Smith, C (Die Naturwissenschaften, 2018)
Providing parental care is potentially costly. Costs can arise through elevated energy expenditure or from an increased risk of mortality. A cost of parental care can also occur because a parent is compromised in their ability to forage. We used pumpkinseed Lepomis gibbosus, a fish with an alternative male mating strategy, to test whether parental males differed in their feeding in comparison with females and cuckolder males. To address this question, we examined the stomach contents of female, cuckolder male, and parental male pumpkinseed during the breeding season over an entire diel cycle. We showed that parental males had a lower total weight of food in their stomachs in comparison with females, while cuckolder males did not. Parental males also had a lower weight and number of chironomids in their stomachs. The temporal pattern of feeding of parental males diverged from that of females, and they had a lower probability of pupal chironomids in their stomachs, which implies spatial segregation in foraging. Parental males had a greater probability of conspecific eggs in their stomachs than females, while the probability of egg cannibalism did not differ between cuckolder males and females. Overall, these finding meet predictions in accordance with an assumption that parental care and territoriality can compromise feeding.
Keywords: otcovské chování; zvířata; Male; Female; Sex Factors; Feeding Behavior; Parental care; Alternative mating strategy; Filial cannibalism; Animals; mužské pohlaví; Bayesian inference; Perciformes; stravovací zvyklosti; ženské pohlaví; Male mating polymorphism; chov; sexuální faktory; Body Size; Territoriality; velikost těla; Paternal Behavior; Breeding